Ework and ebusiness in architecture, engineering and construction : proceedings of the 11th European Conference on Product and Process Modelling (ECPPM 2018), September 12-14, 2018, Copenhagen, Denmark /: proceedings of the 11th European Conference on Product and Process Modelling (ECPPM 2018), September 12-14, 2018, Copenhagen, Denmark. (2018) - Unknown
No abstract available